Majalah Ahkam Johor: Sumbangannya dalam Perkembangan Islam di Johor pada Akhir Abad ke 19: Majalah Ahkam Johor: Its Contribution on Islamic Development in Johor in the Late 19th Century - Othman, Mohd Hafiz; Rozali, Ermy Azziaty; Ismail , Napisah Karimah (Journal of Al-Tamaddun, 2021)
The Majallah al-Aḥkām al-‘Adliyyah belongs to the Ottoman Empire has been introduced in Johor, Malaysia during the reign of Sultan Abdul Hamid II (1876-1908). The book was brought to the Johor Government in 1893 during the reign of Johor’s Sultan Abu Bakar (1862-1895) in its Arabic language and it was translated later into Malay language and Jawi script during the reign of Sultan Ibrahim (1895-1959) in 1913. The translation was done by the Mufti of Johor and it is known as the Majalah Ahkam Johor. The book is a legal reference comprises the civil matters of muamalat, for example sale and purchase, rent and hibah, besides of containing court proceedings too. There are previous studies which affirmed that the Majalah Ahkam Johor was rarely used as a reference in court due to the expansion of colonial British in Malaya. The objective of this paper is to discuss and analyse the challenges of the use of the book in Johor and the obstacles in it’s implementation. The methodology of this study is based on qualitative design with historical research approach and document analysis from primary and contemporary data. The findings of this study shows that the use of the Majalah Ahkam Johor at the court level faced obstacles due to the British administration policy of interfering with the state legal and judicial system. Furthermore, the introduction of British law led to the abandonment of the use of Majalah Ahkam Johor as a reference on Islamic matters in Johor.